2020
DOI: 10.4049/jimmunol.1901166
|View full text |Cite
|
Sign up to set email alerts
|

An Altered Relationship between Soluble TREM2 and Inflammatory Markers in Young Adults with Down Syndrome: A Preliminary Report

Abstract: Individuals with Down syndrome (DS) develop Alzheimer's disease (AD)–related neuropathology, characterized by amyloid plaques with amyloid β (Aβ) and neurofibrillary tangles with tau accumulation. Peripheral inflammation and the innate immune response are elevated in DS. Triggering receptor expressed in myeloid cells 2 (TREM2) genetic variants are risk factors for AD and other neurodegenerative diseases. Soluble TREM2 (sTREM2), a soluble cleavage product of TREM2, is elevated in AD cerebrospinal fluid and posi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4
2

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 75 publications
(86 reference statements)
1
11
0
Order By: Relevance
“…In addition, observation of changing sTREM2 levels in various contexts of neurodegeneration in humans further highlights the importance of TREM2 in human neurological disease and the exciting possibility of therapeutically targeting TREM2. sTREM2 sTREM2 is detected in human cerebrospinal fluid (CSF), and its levels are elevated in CSF of patients with various neurological conditions, such as MS, AD, Parkinson's disease (PD), frontotemporal dementia (FTD) associated with progranulin (GRN) mutations, natural aging in cognitively unimpaired individuals, and in the plasma of Down syndrome patients (Falcon et al, 2019;Heslegrave et al, 2016;Piccio et al, 2008Piccio et al, , 2016Suá rez-Calvet et al, 2016a, 2016bWeber et al, 2020;Woollacott et al, 2018). Matching CSF concentrations of sTREM2 with other measures of human brain function revealed that sTREM2 corresponds to a genetic AD risk status (Deming et al, 2019;Piccio et al, 2016;Suá rez-Calvet et al, 2016a and correlates with disease hallmarks: total tau and phospho-tau181P levels in CSF in AD patients and total tau in PD patients (Heslegrave et al, 2016;Wilson et al, 2020).…”
Section: Diverse Trem2 Roles In Diseasementioning
confidence: 99%
“…In addition, observation of changing sTREM2 levels in various contexts of neurodegeneration in humans further highlights the importance of TREM2 in human neurological disease and the exciting possibility of therapeutically targeting TREM2. sTREM2 sTREM2 is detected in human cerebrospinal fluid (CSF), and its levels are elevated in CSF of patients with various neurological conditions, such as MS, AD, Parkinson's disease (PD), frontotemporal dementia (FTD) associated with progranulin (GRN) mutations, natural aging in cognitively unimpaired individuals, and in the plasma of Down syndrome patients (Falcon et al, 2019;Heslegrave et al, 2016;Piccio et al, 2008Piccio et al, , 2016Suá rez-Calvet et al, 2016a, 2016bWeber et al, 2020;Woollacott et al, 2018). Matching CSF concentrations of sTREM2 with other measures of human brain function revealed that sTREM2 corresponds to a genetic AD risk status (Deming et al, 2019;Piccio et al, 2016;Suá rez-Calvet et al, 2016a and correlates with disease hallmarks: total tau and phospho-tau181P levels in CSF in AD patients and total tau in PD patients (Heslegrave et al, 2016;Wilson et al, 2020).…”
Section: Diverse Trem2 Roles In Diseasementioning
confidence: 99%
“…However, these pro-inflammatory effects were significantly attenuated by TREM2 overexpression, while enhanced by TREM2 silencing. (Li et al 2019) The cleaved soluble TREM2 isoform has been associated with alterations in the immune response in Down syndrome (Weber et al 2020), after exercise (Jensen et al 2019), and AD. (Bekris et al 2018, Brosseron et al 2018, Rauchmann et al 2020) Interestingly, CSF sTREM2 was positively associated with the pro-inflammatory proteins and anti-inflammatory proteins.…”
Section: Introductionmentioning
confidence: 99%
“…The opposite results were reported in a study performed on AD and healthy subjects, where increased levels of CSF sTREM2 were observed in AD patients, particularly in the early stage; however, plasma levels were not different between the two groups, suggesting incorrect plasma sTREM2 levels 11 , 39 . In AD, the plasma sTREM2 levels may not necessarily reflect the CSF sTREM2 levels, and may not follow the same dynamics as CSF sTREM2 33 , 40 . Further studies are required to clarify this.…”
Section: Discussionmentioning
confidence: 99%